The Personality Emotional States` Dynamics in the Context of a Musical Composition Perception - Klimusheva, Hanna; Yanovskaya, Svitlana; Tetska, Polina; Turenko, Rimma (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The article substantiates the need to study the holistic impact of a musical composition on the emotional state of a person, the relevance of which lies in the insufficient study of perception problem in complex combinations of musical stimulus material elements. The aim of the article was to determine changes in the emotional state of a person in the context of a holistic musical composition perception based on universal mythical and cultural motifs of overcoming difficulties. An experimental study was conducted (a simple research design plan for a randomized group with a preliminary survey was used) on a group of 99 participants before and after listening to the musical composition “The Hero’s Journey”, developed based on the work of J. Campbell “The Hero with a Thousand Faces”. The study was implemented using such methods as: E. Diener’s Life Satisfaction Scale, C. Osgood’s Semantic Differential, K. Izard’s Differential Emotion Scale and the Tree picture test. Statistical data processing was carried out using the Wilcoxen signed-rank test for comparing dependent samples, the Mann-Whitney test for comparing independent samples, cluster analysis (k-means method), the Kruskall-Wallis test for comparing independent samples. According to the results of the study, a significant effect of listening to a musical composition on the participants was revealed, which was manifested in the fact that they significantly increased the level of their overall emotional state positivity, the feeling of their internal tone and energy, and also - the intensity of negative grief, anger, disgust, contempt, fear, shame, and depression experiences decreased. In addition, four types of perception of a musical composition were identified, namely: rational, sensual, imagination-oriented, and mixed; however, the effect of a musical composition influence on the emotional state of the listener showed an extremely weak connection with the type of perception of musical material.